Fringe Shakespeare: Shakespeare as You’ve Never Seen It Before - Isabel Guerrero (Atlantis, 2022)
The Edinburgh Festival Fringe has thousands of shows every year and dozens of Shakespeare productions among them. To stand out in the saturated festival market, Shakespeare productions emphasise their popular appeal, rebranding Shakespeare as a simultaneously familiar and, at the same time, new product. The neoliberal market conditions of the festival impose a series of limitations and, consequently, Shakespeare productions need to adjust to time and space restrictions and reduce their casts and sets. Shakespeare productions, therefore, negotiate these constraints in order to attract an audience, a tension that has given rise to specific theatrical approaches to Shakespeare in performance. The main objective of this article is therefore to provide an understanding of Fringe Shakespeare, that is, the theatrical events featuring Shakespeare in performance at the Edinburgh Fringe whose distinctive characteristics are determined by the festival context. To do so, the first part of the article reviews the concept of fringe theatre, examines the tension between innovation and material constraints and explores the reasons why so many companies decide to stage Shakespeare at the Edinburgh Fringe. The second part examines the performing trends in Fringe Shakespeare: appropriations, solo shows, new writing, adaptations into unusual genres and parodies. This will shed light on Fringe Shakespeare and its definition as a theatrical event in the first decades of the twenty-first century.